Academic learning hours post-COVID-19 according to online teaching-learning in higher education - Michal Koren; Roei Zerahia (Springer, 2023)
Abstract Academic institutions have existed for centuries. In most places in the world, classes begin at 8:00 a.m. and continue into the evening hours, usually ending no later than 10:00 p.m. Although online teaching and learning have existed for over a decade, during the COVID-19 pandemic, it was developed and expanded drastically. As a result, new opportunities for innovation in the teaching and learning world were created. One potential opportunity is the exploration of learning hours, which is the topic of this paper. This paper presents a case study of an asynchronous academic course that took place at the end of the pandemic (Spring semester, Q2 of 2022). In this case, the teaching hours were around the clock, as were the learning hours, compared to traditional classes (which are either face-to-face or delivered live online) occurring in the same semester and at the same academic institution. This study aims to raise the question of whether current academic course hours are based on past habits or whether it is necessary to reconsider and adjust the hours to be more suitable for twenty first-century students and according to the need for more flexibility.